"IDEAL" Aging Is Associated with Lower Resting Metabolic Rate: The Baltimore Longitudinal Study of Aging. Issue 4 (17th March 2014) - Schrack, Jennifer A.; Knuth, Nicolas D.; Simonsick, Eleanor M.; Ferrucci, Luigi
<x xml:space="preserve">Abstract</x> Objectives To assess the associations among age, health status, and resting metabolic rate (RMR) in a large population of older adults. Design Cross‐sectional analysis. Setting Community‐dwelling volunteers from the Baltimore Longitudinal Study of Aging (BLSA). Participants Persons aged 40 to 96 (mean 68.2 ± 11.0) who underwent a comprehensive physical examination, cognitive assessment, RMR testing, body composition assessment, and physical function testing during a 3‐day clinic visit (N = 420). Measurements Participants were assigned to Insight into the Determination of Exceptional Aging and Longevity (IDEAL) or non‐IDEAL categories based on health status. IDEAL participants were defined according to the absence of physical and cognitive impairments, chronic conditions and comorbidities, and blood profile abnormalities. A three‐stage linear regression model was used to assess the relationship between RMR and age, using IDEAL classification as a predictor and adjusting for sex and body composition. Results Resting metabolic rate averaged 1, 512.4 ± 442.9 kcal/d and was lower with older age (β = −8.55, P < .001). After adjusting for age, sex, and body composition, RMR was 109.6 kcal/d lower in IDEAL than non‐IDEAL participants (P < .005). Conclusion Individuals who are fully functional and free of major medical conditions have lower RMR than those with disease and functional impairments. These findings suggest that health status plays a role in energy use and regulation independent of age and body composition and that elevated RMR may be a global biomarker of poor health in older persons.